Domestic adoption in Ireland: a shifting paradigm?. (October 2014) - McCaughren, Simone; Lovett, Judy
Domestic adoption in Ireland has been traditionally extremely controversial and its history, linked to the strong influence of the Catholic Church on the Irish state, has left a difficult legacy. In many respects the topography of contemporary domestic adoption in Ireland is now changing, presenting a critical opportunity for a national paradigm shift. However, while there is some evidence of change, a number of factors threaten the potential for more significant progress. Tensions exist between historical adoption practices in Ireland that continue to affect adopted individuals today, contemporary societal perceptions of adoption, the historical and current legislative basis of domestic adoption and the individual needs of those affected by it. The availability of new, independent methods of tracing birth relatives via the internet is competing with the traditional social worker-led model of tracing, creating unforeseen challenges for adoption stakeholders. This article draws on two recent Irish studies in the area of domestic adoption, which examined the experience of adoption, and its inherent challenges, from the perspective of adoptive families, adopted individuals and practitioners. It considers some of the challenges associated with the closed model of adoption and how those directly affected by adoption have been central in highlighting areas in need of reform. Some of the positive changes that have occurred in adoption practice are discussed, and the ongoing tensions that exist between contemporary adoption practice and law are examined.